Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1093/gerona/gln018
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Advanced Glycation End Products and Poor Grip Strength in Older Community-Dwelling Women

Abstract: Background Advanced glycation end products (AGEs) have been implicated in the pathogenesis of diabetes, heart disease, and kidney failure, and may potential affect skeletal muscle. Whether AGEs are associated with poor muscle strength is unknown. Methods Serum carboxymethyl-lysine (CML), a dominant AGE, circulating receptor for AGEs (sRAGE), and endogenous secretory RAGE (esRAGE) and grip strength were measured in 559 moderately to severely disabled women, age ≥65 years, in the Women’s Health and Aging Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 42 publications
(63 reference statements)
6
89
2
1
Order By: Relevance
“…Advanced glycosylation end products AGEs are formed by the nonenzymatic glycosylation of protein adduct and are an important biochemical abnormality found in DM, signifying chronic glucose toxicity. AGEs accumulate in skeletal muscle in patients with DM and have been found to be associated with poor grip strength in older individuals [73]. These products have been postulated to play a role in sarcopaenia by increased inflammation, endothelial dysfunction in skeletal muscle microcirculation and cross-linking of collagen in skeletal muscle [74].…”
Section: Sarcopaeniamentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced glycosylation end products AGEs are formed by the nonenzymatic glycosylation of protein adduct and are an important biochemical abnormality found in DM, signifying chronic glucose toxicity. AGEs accumulate in skeletal muscle in patients with DM and have been found to be associated with poor grip strength in older individuals [73]. These products have been postulated to play a role in sarcopaenia by increased inflammation, endothelial dysfunction in skeletal muscle microcirculation and cross-linking of collagen in skeletal muscle [74].…”
Section: Sarcopaeniamentioning
confidence: 99%
“…Dalal et al [73] Payne et al [74] Mitochondrial dysfunction Recent work has suggested that muscle mitochondrial function is reduced during the process of ageing, and that this may contribute towards insulin resistance. The benefits of exercise in improving insulin resistance have been reported previously; however, it may be that this is mediated at least in part by mitochondrial function.…”
Section: Sarcopaeniamentioning
confidence: 99%
“…In-fact, even if some tendons may be unaffected [33] , there is often evidence of accumulated physical damage in ageing tendons, with increases in the amount of denaturated collagen and increased proteolytic cleavage of matrix components [34] . The effect of ageing on mechanical properties could be due to reduced arterial blood flow, local hypoxia, free radical production, impaired metabolism and nutrition, and advanced glycation end products (AGEs) [35,36] ; such AGEs result from condensation of glucose and amino groups, best observed in diabetic patients [37] . Because the turnover of matrix proteins is generally very low, AGEs accumulate gradually with age [27] .…”
Section: Intrinsic Risk Factors Agementioning
confidence: 99%
“…CML is present in both biological systems, such as plasma, urine, tissues, skin collagen and in many heat-processed foods. Previous studies showed the association between CML accumulation in the human body and diseases like cardiovascular diseases, sarcopenia, and renal diseases (Baumann, 2012;Dalal et al, 2009;Semba et al, 2009a,b). Dietary CML is an important contributor to the body's pool of CML (Luevano-Contreras & Chapman-Novakofski, 2010).…”
Section: Introductionmentioning
confidence: 97%